The influence of another’s actions and presence on perspective taking - Ieva Lukošiūnaitė; Ágnes M. Kovács; Natalie Sebanz (Scientific Reports, 2024)
Abstract The ability to take each other’s visuospatial perspective has been linked to people’s capacity to perceive another’s action possibilities and to predict their actions. Research has also shown that visuospatial perspective taking is supported by one’s own mental own-body transformation. However, how these two processes of action perception and visuospatial perspective taking might interact remains largely unknown. By introducing seven angular disparities between participants and the model in the stimuli pictures across “Action” and “No Action” conditions, we investigated whether the observation of a goal-directed action facilitates perspective taking and whether this facilitation depends on the level of mental own-body transformation required to take perspective. The results showed that action observation facilitated performance independently of the level of mental-own body transformation. The processes behind this facilitation could involve anatomical mapping that is independent of the congruency between the participants’ and the model’s perspectives. Further, we replicated previous research findings, showing that participants were more accurate and faster when taking the perspective of a person compared to an inanimate object (a chair). The strongest facilitation effects were seen at the highest angular disparities between participants and the model in the stimuli pictures. Together, these findings enhance our knowledge of the mechanisms behind visuospatial perspective taking.